PENINGKATAN PENGETAHUAN BIDAN MENGENAI PENATALAKSANAAN INISIASI MENYUSU DINI (IMD) MELALUI VIDEO EDUKASI DI RUANG BERSALIN RSUD CAMPURDARAT KABUPATEN TULUNGAGUNG - Styan Wahyu Diana; Arif Dwi Cahyono; Chusaini Mustas (STIKES ADVAITA MEDIKA TABANAN, 2023)
Early Initiation of Breastfeeding (IMD) is breastfeeding in the first hour of life which begins with skin contact between mother and baby. IMD has been socialized by the government since 2006. This program is called for because the infant and maternal mortality rate during childbirth is still very high. The achievement of IMD at the Campurdarat Hospital still does not meet the minimum target of national achievement. This is due to the lack of knowledge of midwives regarding the management of IMD. If IMD is not implemented, it will have a negative impact on both mother and baby. So it is necessary to have a program to improve the implementation of IMD. The purpose of this study was to determine the difference in knowledge of midwives before and after receiving an educational video about the management of IMD in the delivery room at the Campurdarat Hospital, Tulungagung Regency. This study used a quasi-experimental design with one group pre-test post-test design. The sample of this study was 20 midwives who were selected by total sampling technique. This study begins by giving a pre-test first, then an educational video about the management of IMD is given, and a post test is given at the end of the activity. Data analysis was carried out using the Wilcoxon test, the results obtained p-value = 0.000 < = 0.05, meaning that there was a significant difference in the knowledge of the midwife before and after receiving the educational video. The conclusion of this study was that educational videos were able to increase the knowledge of midwives regarding the management of IMD.